HUBUNGAN KOHESIVITAS DENGAN PARTISIPASI ANGGOTA PADA KELOMPOK TANI TERNAK REJEKI LUMINTU DI KELURAHAN SUMURREJO KECAMATAN GUNUNGPATI KOTA SEMARANG - Ali Musabbikhin; Sriroso Satmoko; Agus Subhan Prasetyo (University of Jember, 2020)
The cohesiveness and participation of members is one element of the dynamics of the farmer group in the process of achieving goals. The ability of Rejeki Lumintu farmer groups to achieve their goals and to face various conditions are influenced by the level of cohesiveness and member participation. Cohesiveness can be a motivation for members to participate. The aims of this study were to determine the level of cohesiveness and participation of group members, as well as the relationship of cohesiveness to member participation in the Rejeki Lumintu farmer groups. The study was conducted in February 2020 in the Rejeki Lumintu Farmer Group, Gunungpati District. This research uses a quantitative descriptive method by scoring answers to the research instruments which are then analyzed statistically to determine the level of cohesiveness and participation as well as the relationship between the two variables. The results show that the level of cohesiveness and member participation was classified as good with a percentage score of 72.2% and 72.8%. There is a relationship between cohesiveness and member participation with a correlation coefficient of 0.905 which is classified as very strong. The relationship that formed makes group participation will increase when cohesiveness has increased. Keywords: Farmer Group, Cohesiveness, Participation